1985
DOI: 10.3109/03009748509165490
|View full text |Cite
|
Sign up to set email alerts
|

Low Selenium Level in Severe Rheumatoid Arthritis

Abstract: Serum selenium concentrations were measured in 87 patients with rheumatoid arthritis. The serum selenium levels of the whole group of patients was significantly reduced (70.2 +/- 13.3 micrograms/l, p less than 0.001) when compared with the reference material (79.8 +/- 10.6 micrograms/l). However, the reduction was not equally pronounced in three groups of patients representing different courses of the disease. One group with an active, disabling disease of long duration had a very reduced serum selenium level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 24 publications
0
20
0
3
Order By: Relevance
“…The results of the present study are in a good agreement with these values, being in the middle of the range. However, one must keep in mind that various disease states may influence the selenium concentration [27][28][29][30], and subjects with specific health conditions were selected for this study. Thus, the results of the present study concern a selected population, but in most of the supermarket chains in Poland the same food products are sold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study are in a good agreement with these values, being in the middle of the range. However, one must keep in mind that various disease states may influence the selenium concentration [27][28][29][30], and subjects with specific health conditions were selected for this study. Thus, the results of the present study concern a selected population, but in most of the supermarket chains in Poland the same food products are sold.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, individuals with health disorders appeared to be the most suitable for this purpose because, as has been described in numerous studies, they tend to have lower selenium concentrations than healthy controls [27][28][29][30] and can hypothetically be more vulnerable to selenium deficit. Therefore, subjects with head and neck cancers, urinary tract cancers and with rheumatoid arthritis were invited to participate in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing titer of naturally occurring IgM could have a protective role based on their ability to bind and neutralize previously unrecognized microbiological antigens, to induce synthesis of acute phase proteins, to interact with cells of adaptive immune response and stimulate the synthesis of antigen specifi c IgG, to suppress infl ammatory responses mediated by innate or adaptive immune cells, and to prevent autoimmune responses mediated by autoimmune B and T cells [24][25][26]. However, knowing that selenium defi ciency is related to the occurrence and progression of some autoimmune diseases (Hashimoto's thyroiditis, rheumatoid arthritis) [5,48,49] and that some autoantibodies belong to naturally occurring IgM pool augment the pathological immune response [24][25][26]50], the recorded increased level of naturally occurring IgM antibodies does not necessarily have a protective role.…”
Section: Discussionmentioning
confidence: 99%
“…Data showed that selenium defi ciency is accompanied with an ineffi cient immune response to various antigens (viruses, tumors, allergens) [3,4], and development of autoimmune diseases [5,6]. Most of its immunomodulatory effects have been explained by its role in antioxidant protection, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It functions in the active site of a large number of selenium-dependent enzymes such as glutathione peroxidase and is associated with anticancer and other physiological functions (Ip et al, 2000;Miller et al, 2001). The lack of Se in food may cause different diseases such as cardiovascular disease (Shamberger et al, 1978), cancer (Schrauzer et al, 1977;Salonen et al, 1984), rheumatoid arthritis (Tarp et al, 1985), cataract (Fecondo & Augusteyn, 1983) and anemia (Chen et al, 1999). The major forms of selenium occurring in foodstuffs are the organic, protein-associated forms, selenomethionine (SeMet, plant and animal sources) and selenocysteine (SeCys, animal sources).…”
Section: Selenium-rich Microalgaementioning
confidence: 99%